2004
DOI: 10.1074/jbc.m408078200
|View full text |Cite
|
Sign up to set email alerts
|

An Annexin 2 Phosphorylation Switch Mediates p11-dependent Translocation of Annexin 2 to the Cell Surface

Abstract: Annexin 2 is a profibrinolytic co-receptor for plasminogen and tissue plasminogen activator that stimulates activation of the major fibrinolysin, plasmin, at cell surfaces. In human subjects, overexpression of annexin 2 in acute promyelocytic leukemia leads to a bleeding diathesis reflective of excessive cell surface annexin 2-de- Investig. 113, 38 -48). Here, we show that endothelial cell annexin 2, a protein that lacks a typical signal peptide, translocates from the cytoplasm to the extracytoplasmic plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
265
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(281 citation statements)
references
References 53 publications
10
265
1
2
Order By: Relevance
“…This was further supported by the finding that depletion of S100A6 in cultured pancreatic cancer cells was found to result in diminished numbers of cells expressing membranous annexin 2. A similar relationship between annexin 2 and S100A10 was reported by Deora et al (2004) who studied the translocation of annexin 2 from the cytoplasm to the cell surface of endothelial cells after the application of mild heat. The authors found that depletion of S100A10 from endothelial cells resulted in reduced surface expression of annexin 2, indicating that S100A10 expression was important for cell surface translocation of annexin 2.…”
Section: Discussionmentioning
confidence: 59%
“…This was further supported by the finding that depletion of S100A6 in cultured pancreatic cancer cells was found to result in diminished numbers of cells expressing membranous annexin 2. A similar relationship between annexin 2 and S100A10 was reported by Deora et al (2004) who studied the translocation of annexin 2 from the cytoplasm to the cell surface of endothelial cells after the application of mild heat. The authors found that depletion of S100A10 from endothelial cells resulted in reduced surface expression of annexin 2, indicating that S100A10 expression was important for cell surface translocation of annexin 2.…”
Section: Discussionmentioning
confidence: 59%
“…SRC kinase can directly phosphorylate ANXA2 on Y23 [26,27], which may negatively modulate ANXA2 function and inhibit the ability of ANXA2 to bind F-actin [27]. However, another study showed that phosphorylation of ANXA2 Y23 is essential for ANXA2 function and its association with the endosome [19].…”
Section: Discussionmentioning
confidence: 99%
“…The ANXA2-S100A10 complex has a channel modulating effect on the cell surface which can affect the membrane interactions of lipids [29]. SRC kinase has been shown to phosphorlyate both ANXA2 [26,27] and S100A10 [30].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, mice with overexpression of p11 had increased 5-HT 1B receptor function and acted as is they were treated with an antidepressant. p 11 also facilitates the translocation of annexin II to the cell surface and the functional expression of ion channels (NaV1.8, TASK-1, TRPV5/6) was shown earlier (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 93%